2022
DOI: 10.1136/bmjopen-2021-057017
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the estimated prevalence of multimorbidity: systematic review and meta-analysis of 193 international studies

Abstract: Objective(1) To estimate the pooled prevalence of multimorbidity in all age groups, globally. (2) To examine how measurement of multimorbidity impacted the estimated prevalence.MethodsIn this systematic review and meta-analysis, we conducted searches in nine bibliographic databases (PsycINFO, Embase, Global Health, Medline, Scopus, Web of Science, Cochrane Library, CINAHL and ProQuest Dissertations and Theses Global) for prevalence studies published between database inception and 21 January 2020. Studies repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 42 publications
6
56
2
1
Order By: Relevance
“…Two key findings were that multimorbidity was consistently higher among women compared to men; and that multimorbidity increased in older age groups. Although female sex has inconsistently been linked to higher levels of multimorbidity in South Africa [ 5 ], the findings on age and sex [ 17 ] are consistent with much of the international literature [ 21 ]. Rising multimorbidity in aging populations has implications for healthcare costs and service utilisation in a country such as South Africa with an ageing population [ 22 ].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Two key findings were that multimorbidity was consistently higher among women compared to men; and that multimorbidity increased in older age groups. Although female sex has inconsistently been linked to higher levels of multimorbidity in South Africa [ 5 ], the findings on age and sex [ 17 ] are consistent with much of the international literature [ 21 ]. Rising multimorbidity in aging populations has implications for healthcare costs and service utilisation in a country such as South Africa with an ageing population [ 22 ].…”
Section: Discussionsupporting
confidence: 65%
“…We included self-reported disease conditions which may underestimate the prevalence as people may have been unaware that they have the disease. However, a recent systematic review indicated no significant difference in the prevalence of multimorbidity when self-report versus clinic/administrative data were used [ 21 ]. Where self-reported disease conditions were included, the way in which the question was asked at times differed.…”
Section: Limitationsmentioning
confidence: 99%
“…For studies of prevalence, we recommend that researchers also report age and sex stratified prevalence based on the "always include" and "always or usually include" lists to improve comparability of studies. 10 More generally, although not the focus of this study, multimorbidity measures are often poorly reported, and clarity about choices made and their rationale is critical (figure 3). 19 We recommend that selection of other long term conditions in measures should take account of the criteria agreed as important by panellists in this study (figure 2), and that researchers explicitly report why and how they make decisions on condition and measurement choice (figure 3).…”
Section: Implications Of Resultsmentioning
confidence: 99%
“…9 The high level of heterogeneity in multimorbidity prevalence has been found to be mainly attributed to age and inconsistent multimorbidity measurement. 10 The estimated pooled prevalence was 68.7% for an oldest population (aged ≥74 years), 26.3% for a younger population (aged >55 years), 29.3% for a measure including fewer than nine conditions, and 87.6% for a measure including 44 or more conditions. 10 Previous studies have synthesised existing evidence on multimorbidity measures, 8 11 12 compared the performance of different measures in predicting selected outcomes, 13 14 and adapted existing measures to meet the professionally perceived needs of specific regions or populations.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation